Maintaining communication between an explorer and a base station - Kutylowski, Jaroslaw (2006)
Consider a (robotic) explorer starting an exploration of an unknown terrain from its base station. As the explorer has only limited communication radius, it is necessary to maintain a line of robotic relay stations following the explorer, so that consecutive stations are within the communication radius of each other. This line has to start in the base station and to end at the explorer. In the simple scenario considered here we assume an obstacle-free terrain, so that the shortest connection (the one which needs the smallest number of relay stations) is a straight line. We consider an explorer who goes an arbitrary, typically winding way, and define a very simple, intuitive, fully local, distributed strategy for the relay stations – our Go-To-The-Middle strategy – to maintain a line from the base station to the robot as short as possible. Besides the definition of this strategy, we present an analysis of its performance under different assumptions. For the static case we prove a bound on the convergence speed, for the dynamic case we present experimental evaluations that show the quality of our strategy under different types of routes the explorer could use.